Chlorophyll a fluorescence induction: Can just a one-second measurement be used to quantify abiotic stress responses? - Stirbet, A.; Lazár, D.; Kromdijk, J.; Govindjee (Photosynthetica, 2018)
Chlorophyll (Chl) a fluorescence induction (transient), measured by exposing dark-adapted samples to high light, shows a polyphasic rise, which has been the subject of extensive research over several decades. Several Chl fluorescence parameters based on this transient have been defined, the most widely used being the F V [= (F M –F 0 )]/F M ratio as a proxy for the maximum quantum yield of PSII photochemistry. However, considerable additional information may be derived from analysis of the shape of the fluorescence transient. In fact, several performance indices (PIs) have been defined, which are suggested to provide information on the structure and function of PSII, as well as on the efficiencies of specific electron transport reactions in the thylakoid membrane. Further, these PIs have been proposed to quantify plant tolerance to stress, such as by high light, drought, high (or low) temperature, or N-deficiency. This is an interesting idea, since the speed of the Chl a fluorescence transient measurement (<1 s) is very suitable for high-throughput phenotyping. In this review, we describe how PIs have been used in the assessment of photosynthetic tolerance to various abiotic stress factors. We synthesize these findings and draw conclusions on the suitability of several PIs in assessing stress responses. Finally, we highlight an alternative method to extract information from fluorescence transients, the Integrated Biomarker Response . This method has been developed to define multi-parametric indices in other scientific fields ( e.g. , ecology), and may be used to combine Chl a fluorescence data with other proxies characterizing CO 2 assimilation, or even growth or grain yield, allowing a more holistic assessment of plant performance.